Multiple Extracranial Metastases from a Rhabdoid Meningioma: A Case Report - Mesquita Filho, Paulo M.; Silva, Rodrigo S.; Annes, Rafael D.; Espanhol, Rafael; Almeida, Timóteo A. de L.; Azambuja, Nério D., Jr. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2015)
Meningiomas are among the most common intracranial primary tumors, and generally have a benign behavior. The incidence of extracranial metastasis of this pathology is low. There are different variants of them, with a wide variety of aggressiveness and potential to metastatic spread. Among the malignant meningiomas (1–3% of total), the rhabdoid variant is known for its aggressive biological and clinical behavior. It is also known that some histological subtypes are inherently prone to recur or spread, as the latter. In the latest World Health Organization classification, extracranial metastases are not currently considered a pathological criterion for malignancy, and, when present, they are most commonly found in the lung, liver, lymph nodes, and bone. Treatment is usually surgical resection of the metastases, but there is still no consensus about it. Owing to its poor prognosis, the rhabdoid subtype is commonly treated aggressively. Patients are submitted to local radiotherapy to prevent recurrence. Extracranial metastases of meningiomas are rare, but should always be remembered, especially in cases of local recurrence and malignant histology, as the rhabdoid variant. We report one case of extracranial metastases in a patient diagnosed with rhabdoid subtype of meningioma, and discuss the literature on this pathology.
Keywords: meningioma; metastatic meningioma; rhabdoid meningioma